Pengaruh Islamic Corporate Governance Dan Islamic Corporate Social Responsibility Terhadap Kinerja Perbankan Syariah - Chintya Zara Ananda; Erinos NR (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to examine the effect of Islamic Corporate Governance and Islamic Corporate Social Responsibility on the performance of Islamic banking. The difference between this study and previous research is the performance measured by Islamic Financial Ratio and profitability ratios. This study uses 63 annual reports from 9 Sharia Commercial Banks listed on the Indonesia Stock Exchange for the 2012-2018 period. Data were analyzed using content analysis methods, descriptive statistics and hypothesis testing with Partial Least Square (PLS), R2 test, t test, and P values. The results showed that Islamic Corporate Governance had a positive and significant effect on the performance of Islamic banking and Islamic Corporate Social Responsibility had a negative effect on the performance of Islamic banking.